A mobile augmented reality-integrated oral health education for community dwelling older adults: A pilot study - Worachate Romalee; Fa-Tzu Tsai; Yi-Chen Hsu; Ming-Lun Hsu; Ding-Han Wang (Elsevier, 2023)
Background/purpose: Providing oral healthcare education can be an optimal strategy for imparting knowledge and developing self-care skills for older adults to enhance their oral health conditions. However, traditional passive lecture-based education programs have several limitations. Integrating mobile augmented reality (MAR) into oral health education can potentially enhance the effectiveness of the education by mitigating those limitations. The objectives of this study are to develop and evaluate the effectiveness of MAR-integrated oral health education. The objectives of this study were to develop and evaluate the effectiveness of MAR-integrated oral health education. Materials and methods: Twenty-four older adults from community dwellings participated in this study. The participants received MAR-integrated oral health education once at activity centers. Self-report questionnaires were utilized to assess oral healthcare-related knowledge and self-efficacy, and the usability score of the MAR system. The assessment was conducted before and after the educational program. Data were statistically analyzed using descriptive statistics and paired-t test. Results: The mean scores of oral healthcare-related knowledge and self-efficacy showed a significant increase after the educational program, with P-values of <0.001 and 0.002, respectively. A majority of the participants exhibited a lack of knowledge and self-efficacy regarding the proper selection of toothpaste and interdental brushes. However, there was an improvement after the intervention. The usability score of the system was lower than the average level. Conclusion: MAR-integrated oral health education effectively increases oral health-related knowledge and self-efficacy among community dwelling older adults. Still, the usability of the MAR system needs to be improved. Further investigation of long-term effects and clinical outcomes, and the inclusion of comparative groups are recommended for the future study.